2020
DOI: 10.1039/d0gc02157a
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable oxidative cleavage of catechols for the synthesis of muconic acid and muconolactones including lignin upgrading

Abstract: Muconic acid and muconolactones are gaining high interest as platform molecules for the synthesis of a variety of compounds, especially in the domain of materials. Despite several technologies have been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…While we analyzed other phenol-degraded intermediates by the purchased products, MU was confirmed by the reaction of DB and Fenton's reagent (Supplementary Materials, Figure S7b). The oxidation of DB produces subsequent intermediates, including cis,cis-muconic acid [24,25]. By comparing the UV spectrum and retention time, we concluded that the intermediate at timepoint 38~39 min of the high-performance liquid chromatography (HPLC) spectrum matches MU.…”
Section: Evaluation Of Intermediates From the Aop Of Phenolmentioning
confidence: 90%
“…While we analyzed other phenol-degraded intermediates by the purchased products, MU was confirmed by the reaction of DB and Fenton's reagent (Supplementary Materials, Figure S7b). The oxidation of DB produces subsequent intermediates, including cis,cis-muconic acid [24,25]. By comparing the UV spectrum and retention time, we concluded that the intermediate at timepoint 38~39 min of the high-performance liquid chromatography (HPLC) spectrum matches MU.…”
Section: Evaluation Of Intermediates From the Aop Of Phenolmentioning
confidence: 90%
“…31,32 Compared with phenolic monomers, the upgrading of catechyl monomers has been less studied. Currently, the main strategy of conversion is to oxidatively open the ring to produce dicarboxylic acids, such as muconic acid 33,34 as well as C3 and C4 dicarboxylic acids if strong oxidation conditions are applied. 35,36 A Fenton-based system using iron ions and hydroperoxide to generate highly oxidative hydroxyl radicals is the most applied method, 33,35 while enzymatic-catalytic oxidation is also practiced.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the main strategy of conversion is to oxidatively open the ring to produce dicarboxylic acids, such as muconic acid 33,34 as well as C3 and C4 dicarboxylic acids if strong oxidation conditions are applied. 35,36 A Fenton-based system using iron ions and hydroperoxide to generate highly oxidative hydroxyl radicals is the most applied method, 33,35 while enzymatic-catalytic oxidation is also practiced. 34 As we are aware, there is no previous report on the direct conversion of catechol and its derivatives into N-heterocyclic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Very recently, Anastas and Darcel reported that four catechol monomers generated from Cu-PMO-catalyzed hydrogenolysis of C-lignin can be converted into muconolactone derivatives through oxidative CÀ C cleavage over the (NH 4 ) 2 Fe(SO 4 ) 2 • 6H 2 O catalyst. [31] To the best of our knowledge, this is the only existing sample for downstream transformation of C-lignin biopolymers, despite the fact that several conversion protocols for pyrocatechol, a potential secondary product from C-lignin, have been proposed and/or practiced. [32][33][34] We recently reported the hydrogenolysis of C-lignin from castor seed coats over an atomically dispersed Ru catalyst (Ru/ ZnO/C), in which a unique propenylcatechol 1 was generated at a high yield with turnover numbers of up to 345 mol catechols mol Ru À 1 .…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the intrinsic features of C‐lignin open a new frontier for the extraction of higher values from lignin because the corresponding end‐chained catechols are essential skeletons in bioactive molecules [29] and functional materials [30] . Very recently, Anastas and Darcel reported that four catechol monomers generated from Cu‐PMO‐catalyzed hydrogenolysis of C‐lignin can be converted into muconolactone derivatives through oxidative C−C cleavage over the (NH 4 ) 2 Fe(SO 4 ) 2 ⋅ 6H 2 O catalyst [31] . To the best of our knowledge, this is the only existing sample for downstream transformation of C‐lignin biopolymers, despite the fact that several conversion protocols for pyrocatechol, a potential secondary product from C‐lignin, have been proposed and/or practiced [32–34] …”
Section: Introductionmentioning
confidence: 99%